Relative Leaf Expansion Rate as an Indicator of Compensatory Growth of Defoliated Vines (Vitis vinifera L. cv. Prokupac) - Cirkovic, D.; Matijasevic, S.; Cirkovic, B.; Bešlić, Z. (South African Journal of Enology and Viticulture, 2023)
Defoliation is a common practice in vineyards, with numerous benefits for vine microclimate conditions, and it can significantly improve the composition of grapes. In addition, early defoliation reduces the active leaf area, which affects the modifications of the source-sink balance and decreases whole-vine photosynthesis. The reaction of grapevines to early defoliation is to mitigate the effects through compensatory growth, resulting in more lateral shoots with a greater number of leaves. In this study, we evaluate the use of nondestructive and continuous measurements of mean and lateral leaf area on the same shoots for the purpose of monitoring leaf area development and calculating relative leaf expansion rate (RLER) during active growth. The results show that the grapevine’s ability to recover its leaf area after defoliation depends mainly on the time of defoliation. Vines defoliated early had time to compensate for the removed leaves by producing a greater number of lateral shoots with more leaves, resulting in a larger total leaf area. With a decrease in shoot growth during vegetation, the recovery ability decreases, and compensatory growth is therefore not enough to restore the reduced leaf area. Based on the value of RLER, it is shown that, if defoliation is performed in the period of intensive shoot growth, it retards the emergence of new shoots and leaves over several days, followed by a period of regrowth. Very slow or no growth of shoots and leaves occurred with defoliation after the véraison stage.